Quality assurance of an established online adaptive radiotherapy program: patch and software upgrade - Bassiri, Nema; Bayouth, John; Chuong, Michael D.; Kotecha, Rupesh; Weiss, Yonatan; Mehta, Minesh P.; Gutierrez, Alonso N.; Mittauer, Kathryn E. (Frontiers in Oncology, 2024)
densities demonstrated comparable agreement between TPS and TDS. ( 7) ART absolute and predicted measured doses was within 1% of calculated TDS.Discussion: An online ART QA program for post-software upgrade has been developed and implemented on an MR Linac system. Testing mechanics and their respective baselines may vary across institutions, but all necessary components for a post-software upgrade QA have been outlined and detailed. These outlined tests were demonstrated feasible for a low-field MR Linac system; however, the scope of this work may be applied and adapted more broadly to other online ART platforms.